REFLECTION OF GENDER LINGUISTICS IN WOMEN'S SPEECH (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about women's speech and its pragmatic realization, which is considered a unique basis of gender linguistics. It should be noted that women's speech differs from men's speech in terms of the inclusion of certain qualities, and this was analyzed as the object of this article.